ANALISIS PERUBAHAN POLA DEKLINASI PADA GEMPA BUMI SIGNIFIKAN (Mâ‰¥7.0) WILAYAH SUMATERA - Indah Fajerianti; Sigit Eko Kurniawan (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Earthquakes are part of the tectonic dynamic process. The process continues in line with changes in the magnitude and direction of the geomagnetic field due to the secular variety. This study aims to review whether there is any change in the pattern of the Geomagnetic declination before and after the occurrence of significant earthquakes (M >= 7. 0) in the Sumatra region during the period 1900 to 2015. The research location is at 6N-10S and 85-110E. The declination data used in the study is based on the International geomagnetic 12 Reference Field (IGRF 12) model within 10 year time span before and after the occurrence of a significant earthquake. Earthquake parameter data are obtained from the catalog of United States Geological Survey (USGS). Forty-one significant earthquakes were recorded and 8 earthquakes are selected as the object of the study. This study uses qualitative analysis by comparing the change in the pattern of declination at a location near the epicenter of an earthquake with a point considered as the region affected by seismic activity. Based on the analysis, the change in declination patterns before and after the occurrence of a significant earthquake is found.Keywords: geomagnetic, declination, earthquakes, Sumatra